Implementation of Corporate Social Responsibility in the Travel Industry in the Development of Sustainable Tourism - Athirah, Andi; Kholmi, Masiyah (Journal La Bisecoman, 2025)
This research examines how Indonesian travel professionals interpret and practice Corporate Social Responsibility (CSR) through sustainable development of the tourism industry. The researchers conducted semi-structured interviews with travel professionals from both management and operations who used qualitative descriptive methods to gather data. The analysis of collected data demonstrated that local ethical conduct drives CSR objectives in this industry instead of standardized formal guidelines. Participants brought forth responsibility factors through how they conducted their regular business activities while maintaining ethical practices toward workers and tourists and showing cultural competence and environmental consciousness together with community involvement. This research disproves conventional CSR standards that prioritize institutionalized reporting systems through its discovery of “relational CSR” based on local cultural values and frontline social interactions. Through their ethical mediatory function tourism operators provide educational services that maintain indigenous cultural value while creating balanced relationships with native communities. The principles of CSR exhibit diverse levels of maturity between businesses although organizations base their practices on authentic moral commitments regardless of weak official backing.